Determination Of Instant Values Of Angular Velocities Observed In The Process Of Operation Of A Feeder For Cotton-Sowing In A Two-Mesh Separator And Control Of Impacting Forces (Texas Journal of Engineering and Technology, 2023)
Instantaneous values of angular velocities are determined during the operation of the device transporting seeded cotton in a double mesh separator. The influencing forces are checked and the ways to eliminate it are considered.